Adherence to Aerosol Therapy in Young People With Cystic Fibrosis: Patient and Parent Perspectives Following Electronic Data Capture. (May 2019) - O'Toole, Daniel P. H.; Latchford, Gary J.; Duff, Alistair J.A.; Ball, Rosemary; McCormack, Pamela; McNamara, Paul S.; Brownlee, Keith G.; Southern, Kevin W.
The benefits of improved treatments for cystic fibrosis (CF) depend on optimal adherence, which remains problematic, particularly to aerosol therapy. In this study, we explored the process of adhering to aerosol therapy from the perspective of both adolescents with CF and their parents. Interviews were conducted individually with six adolescents and six parents, informed by accurate adherence data from an electronically chipped, aerosol device. Interview transcripts from audio-recordings were analyzed using grounded theory method (GTM). Major themes revealed differences in perspective between parent and adolescent, with this relationship mediating the cognitive and emotional processes that play a significant role in adherence behavior. These processes are further influenced by interactions with the aerosol therapy treatment regimen, device characteristics, and the context in which adherence is taking place. Parents and adolescents have different views of treatment and how to manage it. Both need to be addressed if optimal adherence is to be achieved.